A 4-year-old boy with Lemierre's syndrome caused by methicillin-sensitive Staphylococcus aureus - Tahir Hameed; Manal Bawazeer; Nora Alfattoh; Sami Alanazi (Elsevier, 2020)
A pre-school aged boy presented to the Pediatric Emergency Department with a high grade fever and neck pain and stiffness. Blood culture was positive for methicillin-sensitive Staphylococcus aureus (MSSA) and Doppler ultrasound of the neck revealed partial thrombosis of the left internal jugular vein. He was diagnosed with Lemierre's syndrome (LS) and treated with a prolonged course of antibiotics and anticoagulation. After discharge home, he was followed in the outpatient clinics and had a full recovery. This case report will highlight the presentation of LS and will briefly review the microbiology of this condition.